Thioamide Bands and Nature of Bonding in the metal Complexes of 3-(4-Pyridyl)-4-Phenyl Triazoline-5-Thione - Pandey, R.N.; Singh, R.S.P.; Kumari, Rani; Sinha, S.K.; Sahay, A.N. (Asian Journal of Chemistry, 2010)
3-(4-Pyridyl)-4-phenyl-triazoline-5-thione forms very stable complexes with Ag(I). Co(II), Cu(II), Pd(II) and Hg(II) ions at pH 6 or 7. The ligand coordinates through its thione tautomeric form. The nature of shifts and change in intensity of four thioamide bands of the ligand and complexes are thoroughly analysed. The increase in intensity of thioamide band IV in Hg(II)-complexes (pH ∼ 7) probably due to polymeric nature of complexes. The crystal field parameters Dq, B´ β value were found to be 983 cm –1, 702 cm –1 and 0.63 respectively in CO(II)-complexes suggesting the ligand towards strong end of the nephelauxetic series. Tentative structure and metal-ligand vibrations are resasonaly assigned.